Historical dictionary of Hume's philosophy - Coventry, Angela Michelle (Historical dictionaries of religions, philosophies, and movements, 2018)
"This second edition of Historical Dictionary of Hume's Philosophy contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 100 cross-referenced entries covering key terms, as well as brief discussions of Hume's major works and of some of his most important predecessors, contemporaries, and successors"--